Philippines : Financial System Stability Assessment-Press Release and Statement by the Executive Director for the Philippines. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2021)
GDP contracted by 9 1\2 percent in 2020-a much steeper decline than during the Asian Financial Crisis (AFC)-but it is now recovering with the easing of containment measures and economic policy support. Banks are closely connected to the corporate sector through high credit exposures and conglomerate ownership linkages. The Financial Action Task Force (FATF) may list the Philippines as a jurisdiction with serious Anti-Money Laundering and Combatting the Financing of Terrorism (AML/CFT) deficiencies in 2021. The country is also vulnerable to climate change (physical) risks, especially the destruction of physical capital from typhoons.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Philippines